A estrutura organizacional do Partido Socialismo e Liberdade (PSOL) - Morais, Marcelo Maurício de (2017)
The objective of this dissertation is to make an analysis of the training process and institutionalization of the Partido Socialismo e Liberdade (PSOL), to verify his organizational structure as well as understand how this political party emerged under parliamentarian can be propose as reference of left wing political in Brazil. We realize this premise once the Partido dos Trabalhadores (PT), since assuming the Presidency of the Republic, has distanced his originating model and making other spaces for political parties become a reference of the reorganization of the national left. This dissertation justified for the importance that the PT has acquired over the years as a mass political party which proposed as representative of the working class and the others marginalized in the country, and its revolutionary proposal to transform the structure of Brazilian society, equating the insistent social inequality over the years. Analyzing the process of rupture with the PT and the formation of the PSOL, we can observe that over the ten years of his formation, the political party has positioned himself as a party representative of the working class, even if in small sectors of the Brazilian population. Such features are often contradictory, since the Partido Socialismo e Liberdade (PSOL) comes within parliament, and so even has some difficulty to insert social and popular movements of Brazilian society. His originally model, unlike his originated political party, it’s not in social movements, the PSOL begins in the institutional representative landmarks, while the Partido dos Trabalhadores has his origin extra-government. As a source for this dissertation we use documents, interviews, newspaper supporters, news, proceedings of meetings, and proceedings of the National Conference, which made it possible to glimpse their policy guidelines as well as its organizational structure. To complete this dissertation we use wide bibliography that allowed give theoretical basis to our questions